2021
DOI: 10.3389/fdmed.2021.735126
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Interplay Between Periodontal Diseases and COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) is mostly a mild condition, however, in some patients, it could progress into a severe and even fatal disease. Recent studies have shown that COVID-19 infection and severity could be associated with the presence of periodontitis, one of the most prevalent chronic diseases. This association could be explained by the fact that periodontitis and COVID-19 share some common risk factors that included chronic diseases, such as diabetes and hypertension as well as conditions su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…Last, the strong impact of systemic comorbidities in the association between severe COVID-19 and periodontitis may point at some background determinant of vulnerability. A common genetic predisposition to both periodontitis and severe COVID-19 has been advanced by Cai et al (2021), who identified shared genetic phenotypes mainly involving microbial recognition pattern molecules and drivers of inflammation, such as CD26, HLA, and GSTT1-M1. Beyond genes, it cannot be excluded that both severe COVID-19 and periodontitis may occur as 2 pleiotropic outcomes of a gero-vulnerable condition underpinned by high chronic inflammation and immunosenescence (Baima et al 2022).…”
Section: Biological Plausibility: Unraveling the Immune-inflammatory ...mentioning
confidence: 99%
“…Last, the strong impact of systemic comorbidities in the association between severe COVID-19 and periodontitis may point at some background determinant of vulnerability. A common genetic predisposition to both periodontitis and severe COVID-19 has been advanced by Cai et al (2021), who identified shared genetic phenotypes mainly involving microbial recognition pattern molecules and drivers of inflammation, such as CD26, HLA, and GSTT1-M1. Beyond genes, it cannot be excluded that both severe COVID-19 and periodontitis may occur as 2 pleiotropic outcomes of a gero-vulnerable condition underpinned by high chronic inflammation and immunosenescence (Baima et al 2022).…”
Section: Biological Plausibility: Unraveling the Immune-inflammatory ...mentioning
confidence: 99%
“…The target of SARS-CoV-2 infection is cells in the respiratory tract, where Protein S in SARS-CoV-2 will bind to (angiotensin-converting enzyme 2 (ACE2) as the receptor [7]. ACE2 is found in pulmonary epithelial cells, myocardial cells, gastrointestinal system, proximal cells of renal tubules, arterial smooth muscle cells, and oral epithelial cells, where the expression of ACE2 will increase in patients with certain conditions, such as, in elderly individuals, obesity, kidney disease, and lung disease that results in individuals with the condition being more susceptible to the transmission of COVID-19 [8][9][10]. The SARS-CoV-2 virus will replicate, and the virus that has entered the body will be presented by antigens-presenting cells (APCs) and will induce T cells and B cells as humoral and cellular immune responses [11].…”
Section: Covid-19 and Periodontal Diseasementioning
confidence: 99%
“…AP is characterised by increased serum levels of immunoglobulin (Ig)A, IgG, and IgM, 17 whilst periodontitis is characterised by increased levels of ferritin and d -dimer. 28 Given the links between AP and periodontitis, in this study we also investigated possible synergies between these 2 conditions in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%